2015
DOI: 10.1186/s13071-015-1036-6
|View full text |Cite
|
Sign up to set email alerts
|

Invaders, natives and their enemies: distribution patterns of amphipods and their microsporidian parasites in the Ruhr Metropolis, Germany

Abstract: BackgroundThe amphipod and microsporidian diversity in freshwaters of a heterogeneous urban region in Germany was assessed. Indigenous and non-indigenous host species provide an ideal framework to test general hypotheses on potentially new host-parasite interactions, parasite spillback and spillover in recently invaded urban freshwater communities.MethodsAmphipods were sampled in 17 smaller and larger streams belonging to catchments of the four major rivers in the Ruhr Metropolis (Emscher, Lippe, Ruhr, Rhine),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 71 publications
9
112
2
1
Order By: Relevance
“…Microsporidians can be found in most groups of aquatic invertebrates and are also hyperparasites of gregarines, acanthocephalans, cestodes, trematodes and myxozoans (Morris & Freeman, ; Stentiford et al ., ). They were the most diverse and abundant group in the present study, which is in line with previous reports from aquatic organisms, such as amphipods and snails, from which high diversity and prevalence were found (Terry et al ., ; McClymont et al ., ; Krebes et al ., ; Grabner et al ., ). In the present study, some microsporidians were found only in amphipods, but were never detected in insect hosts ( Microsporidium sp.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Microsporidians can be found in most groups of aquatic invertebrates and are also hyperparasites of gregarines, acanthocephalans, cestodes, trematodes and myxozoans (Morris & Freeman, ; Stentiford et al ., ). They were the most diverse and abundant group in the present study, which is in line with previous reports from aquatic organisms, such as amphipods and snails, from which high diversity and prevalence were found (Terry et al ., ; McClymont et al ., ; Krebes et al ., ; Grabner et al ., ). In the present study, some microsporidians were found only in amphipods, but were never detected in insect hosts ( Microsporidium sp.…”
Section: Discussionmentioning
confidence: 97%
“…505 and 515). The same microsporidians were previously detected in different amphipod species (Terry et al ., ; Krebes et al ., ; Grabner, Schertzinger & Sures, ; Grabner et al ., ; Weigand et al ., ), and can be considered amphipod specific. The only unique host–parasite association was found between the mayfly E. danica and the group D‐ Microsporidium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the microsporidians infecting G. roeselii (Table 1) are taxa previously associated with other invasive amphipod hosts [17, 21, 22]. Some unassigned ‘ Microsporidium ’ spp .…”
Section: Introductionmentioning
confidence: 99%
“…Microsporidia are intracellular, obligatory eukaryotic parasites with nonmotile walled spores, belonging to a sister clade to Fungi, Opisthosporidia, which also includes Aphelida and Cryptomycota (Corsaro et al, 2014;Haag et al, 2014;Karpov et al, 2014) and commonly infect amphipod crustaceans (Grabner et al, 2015;Terry et al, 2004). They can be transmitted vertically within the host population (transovarially, from female to offspring) or horizontally (transmission through consumption of infected tissue) causing microsporidiosis (Dunn and Rigaud, 1998;Dunn et al, 2001;Haine et al, 2004) which may be lethal Ryan and Kohler, 2010;Stentiford et al, 2013).…”
Section: Introductionmentioning
confidence: 99%